Deterioration effects of SiO2 nanoparticles on the mass transfer in a single drop system with resistance in both phases. (December 2022) - Roshdi, Sepideh; Kasiri, Norollah; Rahbar-Kelishami, Ahmad
Abstract : In the present study, it has been shown that the very small amount of Nanoparticles(NPs) has very significant effects on mass transfer deterioration. For the first time, the effects of hydrophilic SiO2 NPs have been investigated in the system with the resistance in both phases (butanol-succinic acid-water. NPs with four-volume concentrations were added to the dispersed phase, and the transient and terminal velocities of drops were reported using an image processing tool. Results showed that the effects of NPs on the transient velocity of circulating /oscillating drops are insignificant. Experimental results also showed that the maximum and average deterioration effects were 54% and 26%, respectively in the presence of NPs. The addition of only 0.0005 vol% of NPs revealed about 20% deteriorating effect, while after the addition of 0.01 vol% of NPs, slight differences were observed. Accumulation of NPs in the interface area and gradual occupation were the main reason for mass transfer reduction, which has been supported by the calculation results in the present study. At the final stage, for the first time, the new overall mass transfer correlation has been proposed based on conjugate mass transfer resistance. This general form of correlation can be used for any liquid-liquid extraction (LLE) system with the dominant mass transfer resistance in the two phases in the presence of NPs. Highlights: Investigation of hydrophilic NPs effects on the mass transfer in systems with the resistance in both phases Reporting the mass transfer deterioration of about 20% in the presence of 0.0005 vol% of NPs Proposing a general form of mass transfer correlation for systems with resistance in both phases confirmation of experimental findings with the calculation results